2022
DOI: 10.3389/fcvm.2022.867867
|View full text |Cite
|
Sign up to set email alerts
|

An Olive Oil Mill Wastewater Extract Improves Chemotherapeutic Activity Against Breast Cancer Cells While Protecting From Cardiotoxicity

Abstract: Graphical AbstractThe cartoon summarized the major approaches and insights of the manuscript: (A) the possibility to recover waste material from extra-virgin olive oil (EVOO) processing that allows the repurposing of polyphenol-rich extracts characterized by (B) antiangiogenic activities in vivo, antiproliferative activities in vitro on BC cell lines (C), cardioprotective activities on rat and human cardiomyocytes (HCMs) (D), and in vivo on the zebrafish embryo heart (E).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
(47 reference statements)
0
11
0
Order By: Relevance
“…Integra® Flowable Wound Matrix (FWM), was kindly provided and characterized by LifeSciences Corporation (Plainsboro, NJ, USA). The Cultrex Ultimatrix (Biotechne) (Minneapolis, MN, USA) at 10 mg/ml of concentration was used as matrix for in vivo angiogenesis matrix sponge assay [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…Integra® Flowable Wound Matrix (FWM), was kindly provided and characterized by LifeSciences Corporation (Plainsboro, NJ, USA). The Cultrex Ultimatrix (Biotechne) (Minneapolis, MN, USA) at 10 mg/ml of concentration was used as matrix for in vivo angiogenesis matrix sponge assay [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…In a further study we investigated the anti-cancer effects of A009 on breast cancer cells (MDA-MB-231 and BT-549) when combined with chemotherapeutic agents such as doxorubicin, an anthracycline commonly used in breast cancer therapy, and 5-FU as the prototype fluoropyrimidine. In vitro experiments showed that A009 combined with doxorubicin or 5-FU effectively decreased breast cancer cell growth, and additive effects were observed in breast tumor spheroids ( 38 ). A009 was anti-angiogenic in the Matrigel sponge model containing breast cancer cells supernatants, and recruitment of T cells was increased by A009 ( 38 ).…”
Section: Review Methodologymentioning
confidence: 99%
“…In vitro experiments showed that A009 combined with doxorubicin or 5-FU effectively decreased breast cancer cell growth, and additive effects were observed in breast tumor spheroids ( 38 ). A009 was anti-angiogenic in the Matrigel sponge model containing breast cancer cells supernatants, and recruitment of T cells was increased by A009 ( 38 ).…”
Section: Review Methodologymentioning
confidence: 99%
“…A009, a polyphenolrich Olive mill wastewater (OMWW) extract, was able to counteract the doxorubicin-induced cardiotoxic effects in the zebrafish eAIC model, which is consistent to its cardioprotective activities on rat and human cardiomyocytes. Intriguingly, this waste material from extra-virgin olive oil (EVOO) processing is able to increase the effects of breast cancer chemotherapy via its antiangiogenic and antiproliferative activities (60). While all of these aforementioned compounds are able to rescue cardiac dysfunction to a certain degree, therapeutic target genes for these compounds remain elusive and further mechanistic studies are needed to translate these discoveries to AIC patients.…”
Section: Utilization Of Eaic To Discover Therapeutic Strategiesmentioning
confidence: 99%